Accuracy and precision of cardiac output estimation by an automated, brachial cuff-based oscillometric device in patients with shock. (November 2020) - Papaioannou, Theodore G; Xanthis, Dimitrios; Argyris, Antonis; Vernikos, Pavlos; Mastakoura, Georgia; Samara, Stamatia; Floros, Ioannis T; Protogerou, Athanase D; Tousoulis, Dimitrios
Non-invasive monitoring of cardiac output is a technological and clinical challenge, especially for critically ill, surgically operated, or intensive care unit patients. A brachial cuff-based, automated, oscillometric device used for blood pressure and arterial stiffness ambulatory monitoring (Mobil-O-Graph) provides a non-invasive estimation of cardiac output values simultaneously with regular blood pressure measurement. The aim of the study was to evaluate the feasibility of this apparatus to estimate cardiac output in intensive care unit patients and to compare the non-invasive estimated cardiac output values with the respective gold standard method of thermodilution during pulmonary artery catheterization. Repeated sequential measurements of cardiac output were performed, in random order, by thermodilution (reference) and Mobil-O-Graph (test), in 24 patients hospitalized at intensive care unit. Reproducibility and accuracy of the test device were evaluated by Bland–Altman analysis, intraclass correlation coefficient, and percentage error. Mobil-O-Graph underestimated significantly the cardiac output by −1.12 ± 1.38 L/min ( p < 0.01) compared to thermodilution. However, intraclass correlation coefficient was >0.7 indicating a fair agreement between the test and the reference methods, while percentage error was approximately 39% which is considered to be within the acceptable limits. Cardiac output measurements were reproducible by both Mobil-O-Graph (intraclass correlation coefficient = 0.73 and percentage error = 27.9%) and thermodilution (intraclass correlation coefficient = 0.91 and percentage error = 26.7%). We showed for the first time that cardiac output estimation in intensive care unit patients using a non-invasive, automated, oscillometric, cuff-based apparatus is reproducible (by analyzing two repeated cardiac output measurements), exhibiting similar precision to thermodilution. However, the accuracy of Mobil-O-Graph (error compared to thermodilution) could be considered fairly acceptable. Future studies remain to further examine the reliability of this technology in monitoring cardiac output or stroke volume acute changes which is a more clinically relevant objective.